A facility for thermo-mechanical characterization of fusion magnet materials during cryogenic ion irradiation - Akarsh Aurora; Alexis R. Devitre; Angus P.C. Wylie; Jonas A. Rajagopal; Michael P. Short (Nuclear Fusion)
Commercial fusion power plants demand magnet materials that retain structural integrity and thermal conductivity while operating under neutron bombardment at cryogenic temperatures. Understanding how thermo-mechanical properties evolve under these conditions is crucial for selecting materials with high radiation tolerance and predictable failure mechanisms. Presented here is a facility that combines cryogenic transient grating spectroscopy with simultaneous ion irradiation, enabling in situ measurements of thermal diffusivity and surface acoustic wave (SAW) frequencies, allowing inference of microstructural evolution. Using copper as a benchmark material, an irradiation was performed at 30 K with 12.4 MeV $\text{Cu}^{6+}$ ions producing a fluence of $1.9 × 10^{17}$ ions m ^−2 . Over the irradiation period, thermal diffusivity nearly halved from an initial value of $1.2 × 10^{-4}$ $\text{m}^2\,\text{s}^{-1}$ while SAW speed did not show significant changes, maintaining a value of $2162\,±\,18$ m s ^−1 . Given its real-time monitoring capability and the numerous candidate materials that remain under characterized under fusion magnet operating conditions, this facility is poised to deliver new scientific insights into fusion magnet material degradation trends, contributing to improved design criteria and operational certainty for forthcoming fusion power plants.